Methods to assess bioresorbable vascular scaffold devices behaviour after implantation - Pernigotti, Alberto (J Thorac Dis, 2017)
Bioresorbable vascular scaffolds (BRS) represent a novel approach for coronary revascularization offering several advantages as compared to current generation DES, potentially reducing rate of late adverse events and avoiding permanent vessel caging. Nevertheless, safety concerns have been raised for an increased risk of scaffold thrombosis (ScT) in both early and late phases, probably related to a suboptimal scaffold implantation. In this context, the use of different imaging methodologies has been strongly suggested in order to guarantee an optimal implantation. We herein analyze the different imaging methodologies available to assess BRS after implantation and at follow-up.